A guide to good practice in Mediterranean surface survey projects - Attema, Peter; Bintliff, John; van Leusen, Martijn; Bes, Philip; de Haas, Tymon; Donev, Damjan; Jongman, Wim; Kaptijn, Eva; Mayoral, Victorino; Menchelli, Simonetta; et al. (Journal of Greek Archaeology, 2020)
This article deals with a relatively new form of archaeological research in the Mediterranean region – intensive surface survey, coverage of the landscape by teams walking in close order, recording patterns of human activity visible on the landsurface as scatters of pottery and lithics, or building remains. Since 2000, archaeologists from Dutch and Belgian universities working on Mediterranean survey projects have gathered annually to discuss methodological issues in workshops that gradually attracted landscape archaeologists from other European countries and Turkey. On the basis of these discussions, this paper, written by regular workshop contributors and other invited authors with wider Mediterranean experience, aims to evaluate the potential of various approaches to the archaeological surface record in the Mediterranean and provide guidelines for standards of good practice in Mediterranean survey.